Kabale University Interdisciplinary Research Journal (KURJ) - Kaaya, Siraje; George Stanley, Kinyata (Kabale University Interdisciplinary Research Journal (KURJ), 2023)
The 3rd issue, volume 3 of the KURJ, is published with 8 papers which cover different issues of national, regional and global concern. The papers include: Reverse logistics and environmental sustainability in selected manufacturing entities in Kampala district, Uganda; Antiplasmodial compounds from Millettia dura; Resource mobilisation and allocation priorities on knowledge production in universities in Uganda: an empirical study; Epidemiology and causes of common soccer injuries during university games in Uganda; Micro-credit institution’s services and sustainability of micro, small and medium-scale enterprises during Covid-19 pandemic in Kigezi region south western Uganda; Transformational Leadership style and occupational stress among primary School Teachers in Tanzania; Citrus fruit farmers’ Adaptation Capacities to Climate Variability in Ngora district, Eastern Uganda; Developing metacognition in pre-primary childhood education in Nigeria and Uganda; and Mentorship and supervision in Ugandan higher education Institutions universities: challenges and prospects. The above articles will inform not only academics in these disciplines, but also policy and decision makers.